Menilik Pemanfaatan Antropologi dalam Komunikasi Injil Lintas Budaya - Marde Christian Stenly Mawikere; Sudiria Hura (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article is a conceptual study of the application of anthropology in cross-cultural gospel communication. The research was carried out using a qualitative method which was built from a review of the relevant literature. This study shows important aspects of God, Christ, the Gospel, Man, Society and Culture. The final result of this study shows that with the help of anthropology, a gospel communicator will be able to be creative, dynamic and relevant (contextual) with all aspects of human life and society comprehensively.